1970
DOI: 10.4314/ijest.v3i6.24
|View full text |Cite
|
Sign up to set email alerts
|

Application of design of experiments and artificial neural networks for stacking sequence optimizations of laminated composite plates

Abstract: This paper discusses the use of Distance based optimal designs in the design of experiments (DOE) and artificial neural networks (ANN) in optimizing the stacking sequence for simply supported laminated composite plate under uniformly distributed load (UDL) for minimizing the deflections and stresses. A number of finite element analyses have been carried out using Distance-based optimal design, for training and testing of the ANN model. The deflections and stresses were found by analyses which were done by fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Modifying Sander's shell theory, Reddy and Liu [43] developed a higher-order shear deformation shell theory. The transverse shear strains are assumed to be parabolically distributed across the shell thickness; therefore, no shear correction factors are required in this theory.…”
Section: Nonlinear Dynamics Of Cntrc Cylindrical Shellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifying Sander's shell theory, Reddy and Liu [43] developed a higher-order shear deformation shell theory. The transverse shear strains are assumed to be parabolically distributed across the shell thickness; therefore, no shear correction factors are required in this theory.…”
Section: Nonlinear Dynamics Of Cntrc Cylindrical Shellsmentioning
confidence: 99%
“…where a 11 and a 22 are longitudinal and transverse thermal expansion coefficients, respectively; and Q ij are the transformed elastic constants which are given in details in [43]. Clearly for an FG-CNTRC layer (i.e.…”
Section: Nonlinear Dynamics Of Cntrc Cylindrical Shellsmentioning
confidence: 99%
“…Artificial neural networks have been used by Bezerra et al (2007) to approximate the shear mechanical properties of reinforced composites. Reddy et al (2011) optimized the stacking sequence of laminated composite plates applying neural network. Their work included experimental and finite element analysis for minimizing the deflections and stresses.…”
Section: Buckling Of Laminated Compositesmentioning
confidence: 99%
“…The literature survey revealed that a few analytical methods have been reported for the determination of the studied drugs in pure drug, pharmaceutical dosage forms and biological samples using liquid chromatography either in single or in combined forms [3][4][5], electrochemical methods [6,7], spectroflourimetric methods [3,8] and spectrophotometric methods [9][10][11][12][13][14]. Visible spectrophotometry, because of simplicity and cost effectiveness, sensitivity and selectivity, fair accuracy, precision and available in most quality control laboratories, have remained competitive in an area of chromatography techniques for pharmaceutical analysis.…”
Section: Introductionmentioning
confidence: 99%